Ultraviolet shielding properties of cotton fabric supported by cerium-calcium hydroxyapatite solid solution particles. Issue 15 (September 2014) - Yasukawa, Akemi; Ruike, Sairi; Gotoh, Keiko; Kandori, Kazuhiko
Cotton fabric was supported by three types of cerium-calcium hydroxyapatite (CeCaHap) solid solution particles and the properties were compared. The three types of CeCaHap were prepared using different wet methods. The crystallinity and morphology of the particles were altered depending on the preparation conditions. Because all the CeCaHap particles exhibited a strong ultraviolet (UV) absorption under 400 nm on the ultraviolet-visible spectra, they were supported on cotton fabric by immersing the fabric into the dispersion containing the particles. The treated fabric showed UV shielding properties and fine particles especially showed stronger UV screening properties than large and long particles. With increasing the concentration of the particles in the dispersion, the amount of particles that was supported on the fabric increased and UV screening properties of the fabric were enhanced. The UV shielding ability of the fabric was sufficiently maintained after washing using water or a sodium dodecyl sulfate solution.